Variação linguística da libras no contexto da educação de surdos - Pereira, Karina Ávila (2011)
This master's research aims to analyzethe spread of Brazilian sign language in school environments, and elementary school students have linguistic variations in their speeches. It isdivided in two parts, where the first oneinterviews were conducted with students at a school for the deaf inPelotascity, andstudents in a school withspecific classes of Rio Grande. In the second part, a translator / interpreterof Brazilian sign language-LIBRASof each school was interviewed. Methodologically the research is enrolled in a qualitative approach. Initially a pilot instrument was organized in order to examine whether the methodological tools would be suffi cient to collect data from the signers of LIBRAS,in this case students in upper grades of elementary school, bearing in mind the necessity of adaptation of the instruments commonly used in sociolinguistic research about linguistic variations in sign language and the goals and characteristics of this research. Following the survey, data collected from students in deaf schools and special classes were analyzed by the translators of LIBRASwith the intention of finding linguistic variations. Data from interviews with the translators of LIBRAShave been examined by me and checked with data from the first part. The intersectionwe can conclude that the deaf students make use of linguistic variants in their speech and that the translators of these variations perceiveitas a natural process that occurs in LIBRAS. In addition, it was noticeable that the choice of using a particular variant does not cause any confusion for those students, and that the creation of a new variant is well accepted by the group, as natural process, within acceptable standards for that group. But there is some resistance from teachers in learning many new signs, according to reports of the translators, because some teachers have found it difficult to learn sign language, and with so many variations it seems even harder, showing a weak language and culture in the school environment, for the relations of power in choosing which language to use still revolve around the Portugueselanguage